Effects of pure Acoh and mixed AcOH-CS (CS = CH3CN And THF) solvents on the rate of cleavage of Phthalic Anhydride (PAn) - Ariffin, Azhar; Khan, M.N.; Damit, E.F.; Yusof, N.S.M. (2012)
The values of pseudo-first-order rate constants (k (obs)) for the acetolysis of phthalic anhydride (PAn) increase from 6.60 x 10(-7) to 31.5 x 10(-7) s(-1) with the increase in temperature from 30 to 50 A degrees C. These values of k (obs) give activation parameters a dagger H* and a dagger S* as 14.4 +/- A 0.4 kcal mol(-1) and -39.1 +/- A 1.3 cal K-1 mol(-1), respectively. The values of k (obs) remain essentially unchanged with the increase in the content of CS (CS = CH3CN or THF) from 0 to 40 % v/v in mixed AcOH-CS solvents. These observations have been explained qualitatively.